HEAR - Mandic, Danilo; Nirta, Caterina; Pavoni, Andrea; Philippopoulos-Mihalopoulos, Andreas (University of Westminster Press, 2023)
Hearing is an intricate modality of sensory perception. It is continuously enfolded in the surroundings in which it takes place. While passive in its disposition, hearing is integral to the movement and fluctuations of one's environment. At all times, hearing remains open, (in)active but attuned to the present and continuously immersed in the murmur of its background. A delicate perception that is always situated but fundamentally overarching and extended into the open. Hearing is an immanent modality of being in and with the world. Beyond the capacity of sensory perception, hearing is also the ultimate juridical act, a sense-making activity that adjudicates and informs the spatio-temporal acoustics of justice. This penultimate volume of 'Law and the Senses' gathers contributions from across different disciplines working on the relationship between law and hearing, the human vocalisations and non-human echolocations, the spatial and temporal conditions in which hearing takes place, as well as the forms of order and control that listening entails. Through notions and practices of improvisation and noise, attunement and audibility sonic spatiality and urban sonicity they explore, challenge and expand the structural and sensorial qualities of law. Moreover, they recognise how hearing directs us to perceiving and understanding the intrinsic acoustic sphere of simultaneous relations, which challenge and break the normative distinctions that law informs and maintains. In an attempt to hear the ambiguous, indefinable and unembodied nature of hearing, as well as its objects - sound and silence - this volume approaches hearing as both an ontological and epistemological device to think with and about law.